Systems Biology Modeling to Study Pathogen-Host Interactions - Cesur, Muberra Fatma; Durmus, Saliha (Humana Press Inc, 2018)
Pathogen-host interactions (PHIs) underlie the process of infection. The systems biology view of the whole PHI system is superior to the investigation of the pathogen or host separately in understanding the infection mechanisms. Especially, the identification of host-oriented drug targets for the next-generation anti-infection therapeutics requires the properties of the host factors targeted by pathogens. Here, we provide an outline of computational analysis of PHI networks, focusing on the properties of the pathogen-targeted host proteins. We also provide information about the available PHI data and the related Web-based resources.
Keywords: Pathogen-host interaction; Network analysis; Comparative interactomics; Infection mechanism; Drug target